Pendidikan Pengenalan Gender pada Anak Usia Dini dengan Metode Bermain Peran di RA Al Mustaqbal - Shabirah Nafisah; Lily Yuntina; Sudi Suhardjo (Indo Publishing, 2025)
This research aims to introduce the concept of gender to early childhood, as gender awareness education is closely related to social development and the formation of behavior patterns in adulthood, as well as helping children fully understand their self-identity as male or female. The study focuses on preliminary observations conducted at RA Al Mustaqbal regarding early childhood gender understanding, particularly in self-identification. Through role-playing, children can explore various roles without being limited by gender stereotypes, allowing them to develop talents, interests, and hobbies freely regardless of sex. This method also enhances children’s socio-emotional aspects, such as self-confidence, tolerance, and social skills. Educators also gain insights into inclusive gender values that can be internalized in the learning process, thereby creating a gender-equitable early childhood education environment that supports holistic child development. The method used in this study is a descriptive qualitative approach, as it is highly suitable and relevant to the research entitled “Gender Awareness Education for Early Childhood through Role-Playing Method at RA Al Mustaqbal.” Data collection techniques include observation, interviews, documentation, and photography. To ensure the validity of the data, source triangulation was applied. The findings at RA Al Mustaqbal show that the role-playing method is an effective way to introduce gender education to early childhood. Through role-playing activities, children are given opportunities to engage directly in various simulations of professional or daily life roles without restrictions based on gender. Both boys and girls are free to choose and perform roles they are interested in, enabling them to experience firsthand being, for example, a doctor, teacher, police officer, firefighter, or other professions. Participation in role-play has proven to encourage a more open attitude and acceptance of diverse gender roles. Children become more confident, willing to try roles outside their usual choices, and begin to understand that any role can be carried out by anyone regardless of gender identity. Social interactions during these activities also help sharpen communication, cooperation, and empathy—key aspects in character building and fostering gender equality awareness from an early age. Teachers at RA Al Mustaqbal play a crucial role in designing, guiding, and creating an inclusive environment throughout the role-playing process. With positive atmosphere and constructive guidance from teachers, children are better able to comprehend the concept of gender awareness education.